Development of development of a sensitive magnetometer (eddy current probe) prototype for defect evaluation in steel components - Saari, Mohd Mawardi; Nurul A’in, Nadzri; Aiman, M. H. (2019)
Cracks are known as one of the defects that usually happen within a steel structure such as piping, funnel, bridges, buildings and other civil engineering structures, and can occur on the surface or subsurface of the structures. Detection of crack is crucial since cracking can cause dangerous damage to the structure which may lead to structural collapses and unfortunate events. Therefore, cracking needs to be discovered earlier before it reaches the point of fracture. Moreover, the method that is used to inspect the materials or components should not compromise the functionality of the specimen under test. It is also required that the method should provide contactless crack detection technique. Thus, for this reason, the non-destructive testing (NDT) methods are beneficial to fit those requirements as they are widely used in industries in order to control the quality of materials. Since NDT is becoming popular and necessary in certain conditions, there are few methods or techniques that have been founded in order to detect cracks based on different physics principles. Among them, magnetic method is one of the favorable methods in NDT especially in metal industries in order to evaluate the crack without causing any damage to the subject. One of the techniques based on the magnetic method, which is applied regularly to inspect metal structures, is the eddy current testing (ECT) method. This research presents the study and detailed analysis of an ECT probe’s development based on AMR sensors for identifications of defects in galvanized steel plates. The probe consists of an excitation coil which is used to induce eddy current in sample plates and two AMR sensors to detect the differential magnetic response induced by eddy currents. Moreover, this probe is connected to a set/reset circuit and a homemade instrumentation amplifier circuit. In order to analyze the magnetic field distribution, which is detected by the AMR sensors, a phase sensitive detection technique by using a lock-in amplifier is applied. When the sensor probe is introduced to a metal plate with defect, the induced eddy current loops in the metal will be interfered, then it will cause changes in the magnetic field distributions. The performance of the ECT probe in the crack detection is evaluated using artificial slits on 2-mm galvanized steel plates. The performance is classified to the depth, width, length and complex shapes of slits, and the probe is used to perform line-scans and 2-D map scans above the slits’ positions. By using the developed ECT probe, the magnetic response is measured on the surface and backside of the 2-mm galvanized steel plates. The output signal is detected and analyzed using imaginary components of the magnetic response vectors. The captured data show a signal change at the crack position. From the results, it can be said that the ECT probe can detect the crack as small as 0.05 mm. Furthermore, the shape of the slits can be estimated based on the distribution patterns of the differential magnetic response. It can be expected that the developed system will play an important role in the crack detection in future.